2021
DOI: 10.7150/ijms.51164
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Targeted Gut Microbiota with Body Composition in Type 2 Diabetes Mellitus

Abstract: The association between body composition and gut microbiota in type 2 diabetes mellitus (DM) remains unknown. To elucidate the correlation of body composition and gut microbiota, we conducted a clinical study to enroll 179 patients with type 2 DM. Body composition of lean tissue index (LTI) and fat tissue index was measured by Body Composition Monitor. Eight pairs of 16S rRNA gene primers specific to Firmicutes, Bacteroidetes, the Clostridium leptum group, Bacteroides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 51 publications
0
33
0
2
Order By: Relevance
“…Among the common bacterial communities, Bacteroidetes, Firmicutes, Proteobacteria, Actinobacteria, and Verrucomicrobia were the main five phyla present in the gut microbiota of all groups (Figures 6A,B). Many studies have shown that obesity and diabetes mellitus are closely related to the ratio of Firmicutes to Bacteroidetes (Ley et al, 2005;Grigor'eva, 2020;Hung et al, 2021). However, the results revealed a slight increase of the Firmicutes/Bacteroidetes ratio in db/db mice than in WT mice at each age, but without significant difference (Figure 6C).…”
Section: Differentially Represented Bacterial Taxa In Db/db Micementioning
confidence: 86%
“…Among the common bacterial communities, Bacteroidetes, Firmicutes, Proteobacteria, Actinobacteria, and Verrucomicrobia were the main five phyla present in the gut microbiota of all groups (Figures 6A,B). Many studies have shown that obesity and diabetes mellitus are closely related to the ratio of Firmicutes to Bacteroidetes (Ley et al, 2005;Grigor'eva, 2020;Hung et al, 2021). However, the results revealed a slight increase of the Firmicutes/Bacteroidetes ratio in db/db mice than in WT mice at each age, but without significant difference (Figure 6C).…”
Section: Differentially Represented Bacterial Taxa In Db/db Micementioning
confidence: 86%
“…The detailed methods were described previously [ 33 ]. In brief, fecal samples were collected at the same day of blood and urine collection.…”
Section: Methodsmentioning
confidence: 99%
“…We used real-time qPCR in a StepOnePlus Real-Time PCR system (Thermo Fisher Scientific, Waltham, MA, USA) to detect bacterial 16S rRNA gene copies in stool according to a previous study [ 26 , 33 ]. The 8 pairs of 16S rRNA gene primers specific to Firmicutes , Bacteroides , the C. leptum group , F. prausnitzii , Bifidobacterium , E. coli , and A. muciniphila are listed in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the aforementioned positive effects of regular physical activity on glycemic control/insulin sensitivity, exercise training (together with other lifestyle changes) is known to contribute to changes in body composition (increases in muscle mass and reductions in fat mass) [37,38]. It is important to note that a changed body composition can result in a different microbiome composition [39].…”
Section: Influence Of Exercise Training On the Gut Microbiota And The...mentioning
confidence: 99%